Overview of research on teacher self-efficacy in social cognitive perspective - Oliveira Fernandez, Ana Patrícia; Ramos, Maély Ferreira Holanda; Silva, Simone Souza Costa; Nina, Karla Cristina Furtado; Pontes, Fernando Augusto Ramos (Anales de Psicología / Annals of Psychology, 2016)
The objective of this work was to systematically review existent researches about teacher self-efficacy. For this purpose, searches are performed on the data basis of CAPES – periódicos between 2009 and 2013. The survey resulted on 26 articles that contemplated the criteria of inclusion previously established. The results of the studies indicate that self efficacy is influenced by factors as emotional exhaustion, depersonalization, job satisfaction, relationship with parents, use of violence, pressures of time, academic performance, class management, collective efficacy, among others. Such results contribute to sign the direction of researches performed in the area, indicating some trends and evidencing gaps to be investigated, for example, a larger number of studies that verify the relation between self efficacy and academic performance, as well as, teacher self efficacy and public policies that favor the process of teaching-learning.